2018
DOI: 10.1016/j.bjorl.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorder: otologic implications and its relationship to sleep bruxism

Abstract: The logistic regression analysis demonstrated strong associations between the disorder and both otologic symptoms and bruxism when analyzed simultaneously, independently of patient age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
3
15
0
6
Order By: Relevance
“…According to Berger et al [29] and Magalhães et al [30], bruxism compromises the masticatory system and is considered a major etiological factor in TMD. A common condition in patients with TMD, it is predominantly associated with muscle disorders, but can also be attributed to temporomandibular joint (TMJ) dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Berger et al [29] and Magalhães et al [30], bruxism compromises the masticatory system and is considered a major etiological factor in TMD. A common condition in patients with TMD, it is predominantly associated with muscle disorders, but can also be attributed to temporomandibular joint (TMJ) dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Magalhães et al [30] reported that 52% of individuals with TMD exhibited bruxism and those with bruxism were twice as likely to develop TMD. These studies corroborate our findings, in which 76% of women with TMD reported suffering from bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings described in previous studies, in which the larger portion of the sample was composed of women. 6,7,12,20,[22][23][24][25][26][27] To explain…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of patients in relation to age and the presence of otological symptoms (N=516), Curitiba, Paraná, 2017 Stechman NJ, Porporatti AL, Toledo IP, Costa YM, Conti PCR, Canto GL et al Effect of this finding, some authors have proposed a possible relationship between TMD and mechanisms of pain modulation, since women exhibit greater sensitivity to pain, as well as environmental, social and cultural factors.16,22,27,28 …”
mentioning
confidence: 99%
“…17,18 Bu çalışmanın amacı kliniğimize temporomandibular eklem disfonksiyonu şikayetleriyle başvuran hastalarda eklem ağrısı ile migren, tinnitus, baş dönmesi/ağrısı, duyma kaybı, omuz/boyun ağrısı bulguları arasındaki ilişkinin değerlendirilmesidir. 19 Ağrı yaratan durum, TME tarafında kompanse edilip fonksiyon anlamında kısa vadede bir sorun ile karşılaşılmasa bile zamanla bu durum TMED gelişimini tetiklemektedir. 20 Literatürde, TME hastalarında en sık belirtilen semptomlar; kulakta çınlama, otalji, kulakta doluluk hissi, işitme kaybı ve baş dönmesidir.…”
Section: Gġrġġunclassified